Enabling Situation-Aware Behavior in Web-Based Learning Systems - Pernas, A. M.; Palazzo Moreira de Oliveira, Jose (2011 30th International Conference of the Chilean Computer Science Society, 2011)
Adaptive systems need to be aware about the user context and the occurrence of specific events to properly react to. In particular, web-based educational systems have to be improved in order to consider the learner in his/her current situation. Thus, the main objective of this paper is to present a system able to recognize the situations configured in an e-learning environment, aiming at suggesting better actions to be followed by students each time are necessary, for example, when the learner encounters a difficulty to solve an exercise or spend a lot of time to finish a course. In this work, our solution is developed as an extension of an already functional learning environment, called AdaptWeb®, and enables situation-aware behavior customized to its audience. The main challenge is monitoring events and detecting situations.